"Is 'junk food' an 'healthy' concept?" the challenges of the current debate. Issue 8 (29th July 2014) - Finardi, Corrado; Tognon, Gianluca
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The term "junk food" is for the most part currently used in the widest political and media debate, without reference to something tangible. The purpose of this paper is to pinpoint the delicate issues involved in moving towards a trans-national, unified, consensual definition of the term "junk food", including social, economic, cultural, nutritional and methodological problems. Design/methodology/approach – Departing from the work done by international bodies (WHO, FAO-Codex Alimentarius, OECD, EFSA and European Commission) authors descriptively investigate possible background elements able to frame the surrounding debate about "junk food" ("nutrient profiles", labelling provisions, institutional aspects, etc.). Findings – Presently there is a lack of a global consensus and of scientific basis to define clearly what constitutes "junk food" either on regional areas or globally. Despite of good metrics able to classify foods according to their nutritional quality, policy making relies yet on the concept that only diets or single nutrients can be focused as "good or bad". Practical implications – A "junk food" taxonomy could be helpful to harmonize trade policies in internal markets (i.e. the EU) and at global level; but also to gain a wider social support for "hard" policy measures intending to counteract non-communicable-diseases (NCDs), and more generally, obesity and overweight. Social implications – A clear basis for "junk food" definition could be the first step to introduce otherwise controversial and easily opposable public health policies and campaigns, due to private interests of the different stakeholders. Even consumers may perceive food policies (in the sake of "food taxes" or "traffic light labelling") as unfair, whereas not robust scientific ground has been previously given at the highest possible level. Originality/value – The value of this descriptive paper consists in addressing the shortcomings of global and regional nutritional policies framework in front of the emerging trend of "globesity". Conclusions stress the need to find support for broader food policies (labelling, taxes, education, bans, etc.) which currently are on the rise but lack fundamental aspects of scientific and hence social support.